Counterfeit Pesticides for Your Pet - Frederick M. Fishel (EDIS)
PI-172, a 2-page illustrated fact sheet by Frederick M. Fishel, describes how to identify pet pesticide products that are not legitimate, how to properly dispose of them, and what to do if you suspect you have counterfeit pesticide products. Includes additional sources of information. Published by the UF Pesticide Information Office, Department of Agronomy, October 2008.